2022
DOI: 10.3389/fmicb.2022.964855
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of acetic acid bacteria and lactic acid bacteria in multispecies solid-state fermentation of traditional Chinese cereal vinegar

Abstract: The microbial community plays an important role on the solid-state fermentation (SSF) of Chinese cereal vinegar, where acetic acid bacteria (AAB) and lactic acid bacteria (LAB) are the dominant bacteria. In this study, the top-down (in situ) and bottom-up (in vitro) approaches were employed to reveal the interaction of AAB and LAB in SSF of Shanxi aged vinegar (SAV). The results of high-throughput sequencing indicates that Acetobacter pasteurianus and Lactobacillus helveticus are the predominant species of AAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…In the co-occurrence network analysis, due to significant microbial community variations among the seed Pei samples, we only observed correlations between five core microorganisms involved in vinegar fermentation. This finding indicates a negative correlation between the key acid-producing microorganisms, such as Acetobacter and Lactobacillus , which aligns with previous studies on vinegar microbiota (Hutchinson et al, 2019 ; Chai et al, 2020 ; Xia et al, 2022 ). Furthermore, our review of previous research reveals a consistent trend of competitive dynamics between Acetobacter and Lactobacillus in different vinegar production processes (Wang et al, 2016 ; Nie et al, 2017 ; Huang et al, 2022 ; Li et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the co-occurrence network analysis, due to significant microbial community variations among the seed Pei samples, we only observed correlations between five core microorganisms involved in vinegar fermentation. This finding indicates a negative correlation between the key acid-producing microorganisms, such as Acetobacter and Lactobacillus , which aligns with previous studies on vinegar microbiota (Hutchinson et al, 2019 ; Chai et al, 2020 ; Xia et al, 2022 ). Furthermore, our review of previous research reveals a consistent trend of competitive dynamics between Acetobacter and Lactobacillus in different vinegar production processes (Wang et al, 2016 ; Nie et al, 2017 ; Huang et al, 2022 ; Li et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…From the results, it could be inferred that the addition of Lactobacillus helveticus , Lh-43 or Lactobacillus plantarum , Lp-28 to bicultural form of Lactobacillus casei , Lc-122 and Acetobacter pasteurianus , Ap-As.1.41 could significantly improve the TPC of jujube puree (408.28 ± 0.38 or 493.41 ± 1.23 versus 397.54 ± 1.07 mg GAE/100 g, FW respectively). Substantial decrease and marginal increase (p <0.05) respectively in TPC of purees produced from Lactobacillus helveticus , Lh-43 (443.07 ± 2.40 mg GAE/100 g, FW) in combination with either Lactobacillus casei , Lc-122 (408.28 ± 0.38 mg GAE/100 g, FW) or Lactobacillus plantarum , Lp-28 (445.01 ± 0.72 mg GAE/100 g, FW) in the presence of Acetobacter pasteurianus , Ap-As.1.41 could probably be expected based on previously published studies of Xia et al [ 20 ], who emphasized that Lactobacillus helveticus and Acetobacter pasteurianus are frequently isolated fermenters in vinegar especially, cereals. Nevertheless, Lactobacillus plantarum , Lp-28 when tri-cultured with Lactobacillus helveticus , Lh-43 and Acetobacter pasteurianus , Ap-As.1.41 significantly improved the TPC of the fermented purees compared to bicultural form of Lactobacillus plantarum , Lp-28 and Acetobacter pasteurianus , Ap-As.1.41 (445.01 ± 0.72 versus 414.93 ± 0.38 mg GAE/100 g, FW respectively).…”
Section: Resultsmentioning
confidence: 61%
“…Numerous microbial interactions may take place during multispecies food fermentation. The cohabitation of microorganisms in the same ecological niche can result in favorable or unfavorable interactions, impacting their growth patterns, capacity for adaptation, and capacity to manufacture metabolites [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with studies from other fermented foods that have shown that AAB lower the pH of their environment (6, 7). The release of acetic acid and corresponding decrease in pH may inhibit the growth of other species and aid in AAB persistence (52). While pH was lowered in all AAB treatments, there were significant differences between species, including between strains of closely related species.…”
Section: Resultsmentioning
confidence: 99%